Penspesifikasian dan pengesahsahihan formal protokol CSMA/CD menggunakan Z - Zarina Shukur,; Nursyahidah Alias,; Bahari Idrus,; Mohd Hazali Mohamed Halip, (2009)
This paper discusses the formal specification and validation for CSMA/CD protocol. The Z specification language is used to specify a node in a network and a situation in a bus implementation for CSMA/CD protocol. One basic type, four free types, one global variables, two state schemas and nine operation schemas that represent CSMA/CD protocol have been specified by using the Z language. The specification has been validated by using theorem proving techniques supported by Z/EVES theorem prover. Nine theorems have been identified based on the nine specified operations. This study has shown that, Z has the ability to specify a communication protocol. Beside that, the usage of support tools during a proving process can save time dan energy, and reduce error-prone.